2019
DOI: 10.1093/cid/ciz010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune Responses in Humans During Nipah Virus Acute and Convalescent Phases of Infection

Abstract: Background Nipah virus (NiV) is 1 of 10 potential causes of imminent public health emergencies of international concern. We investigated the NiV outbreak that occurred in May 2018 in Kerala, India. Here we describe the longitudinal characteristics of cell-mediated and humoral immune responses to NiV infection during the acute and convalescent phases in 2 human survivors. Methods Serial blood samples were obtained from the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
4
17
1
Order By: Relevance
“…Interestingly, a recent study examining B and T cell populations in two survivors of NiV infection in India [31] identified activation of both CD4+ and CD8+ T cells and proliferation (Ki67+) of CD8+ T cells in a response that is similar to that seen in the surviving animal in the study reported here. While the survivor study examined a very limited population (n = 2) and the study reported here identified only a single NHP survivor, the correlations between the human and NHP B and T cell responses is compelling and potentially identifies key correlates of protective immunity.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, a recent study examining B and T cell populations in two survivors of NiV infection in India [31] identified activation of both CD4+ and CD8+ T cells and proliferation (Ki67+) of CD8+ T cells in a response that is similar to that seen in the surviving animal in the study reported here. While the survivor study examined a very limited population (n = 2) and the study reported here identified only a single NHP survivor, the correlations between the human and NHP B and T cell responses is compelling and potentially identifies key correlates of protective immunity.…”
Section: Discussionsupporting
confidence: 76%
“…This observation is further supported by studies in a pig model for NiV infection showing substantial activation of CD8 T cells after oral infection with NiV [45]. In line with these preclinical data, humans surviving NiV infection [2] showed significant levels of proliferating (Ki-67+) CD8 T cells, indicating the presence of acute effector cells. These data emphasize that in addition to the humoral immune responses, T cells could be associated with recovery from NiV infection.…”
Section: Discussionsupporting
confidence: 65%
“…Of note, a soluble version of NiV-G was advantageous in activating NiV-G-specific cellular immune responses using these peptides. the first time NiV emerged in southern India [2]. Two strains of NiV have been identified, Malaysia and Bangladesh strains, which share 91.8% sequence homology [3].…”
mentioning
confidence: 99%
“…Virus clearance from the blood coincided with peak CD8 T cell activation and the appearance of KFDV-specific IgG. Significant CD8 T cell activation was noted during the acute phase of KFD, as has been noted during infection or after vaccination with dengue, yellow fever, tick-borne encephalitis, Nipah, Ebola, and Lassa viruses, among others [14][15][16][17][18][19] . Activated (Ki67 +) CD8 T cells expressed high levels of acute effector markers PD-1 and CLTA-4 and cytotoxic molecules such as granzyme B and perforin, as well as low levels of Bcl-2, and CD45RA, suggesting that these effector cells were recruited from the naïve population via antigen-specific activation.…”
Section: Discussionmentioning
confidence: 57%